2021
DOI: 10.1038/s41398-021-01235-8
|View full text |Cite
|
Sign up to set email alerts
|

Orexin receptor antagonists reverse aberrant dopamine neuron activity and related behaviors in a rodent model of stress-induced psychosis

Abstract: Post-traumatic stress disorder (PTSD) is a prevalent condition affecting approximately 8% of the United States population and 20% of United States combat veterans. In addition to core symptoms of the disorder, up to 64% of individuals diagnosed with PTSD experience comorbid psychosis. Previous research has demonstrated a positive correlation between symptoms of psychosis and increases in dopamine transmission. We have recently demonstrated projections from the paraventricular nucleus of the thalamus (PVT) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 67 publications
(96 reference statements)
7
19
0
Order By: Relevance
“…These studies provide preclinical evidence that targeting α5-GABA A Rs may represent an effective treatment for psychosis. Although aberrant dopamine neuron activity and deficits in PPI are also observed in animal models used to study PTSD ( Elam et al, 2021 ), the underlying pathology likely differs and whether the efficacy of therapeutic approaches is consistent across diagnosis is not currently known. Nonetheless, we posit that augmenting hippocampal interneuron function by targeting α5-GABA A Rs will correct this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide preclinical evidence that targeting α5-GABA A Rs may represent an effective treatment for psychosis. Although aberrant dopamine neuron activity and deficits in PPI are also observed in animal models used to study PTSD ( Elam et al, 2021 ), the underlying pathology likely differs and whether the efficacy of therapeutic approaches is consistent across diagnosis is not currently known. Nonetheless, we posit that augmenting hippocampal interneuron function by targeting α5-GABA A Rs will correct this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…4 A ) that begins with projections to the NAc ( Lodge and Grace, 2011a ; Perez and Lodge, 2018 ). Importantly, increased activity in glutamatergic projections from the vHipp and PVT to the NAc has been observed in a variety of rodent models of psychiatric disorders, including PTSD ( Elam et al, 2021 ) and schizophrenia ( Perez and Lodge, 2013 ; Boley et al, 2014 ), and this hyperactivity results in increased dopamine neuron population activity in the VTA. Previous research has demonstrated that selective inactivation of the vHipp or PVT in rodent models used to study psychosis can restore normal dopamine system function ( Lodge and Grace, 2007 ; Perez and Lodge, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The orexin system was first discovered to regulate sleep (wakefulness) and appetite but recently studies revealed its role in pain regulation, cardiovascular function, neuroendocrine modulation, and other biological processes [ 21 , 38 ]. Orexin receptor antagonists have shown great promise in treatment of insomnia, substance use disorder and psychosis [ 39 - 41 ]. Suvorexant, almorexant, and several other dual and single orexin receptors antagonists promote sleep in humans and are commercially available in the market [ 39 - 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Orexin receptor antagonists have shown great promise in treatment of insomnia, substance use disorder and psychosis [ 39 - 41 ]. Suvorexant, almorexant, and several other dual and single orexin receptors antagonists promote sleep in humans and are commercially available in the market [ 39 - 46 ]. In demyelinating diseases such as MS, healthy sleeping patterns is disrupted [ 47 ]; oligodendrocyte proliferation and/or differentiation and lipid biogenesis patterns are altered throughout sleep and wakefulness [ 48 ].…”
Section: Discussionmentioning
confidence: 99%